Pengaruh Partisipasi Politik Terhadap Pemilih Pemula Menjelang Pemilihan Umum 2024 Di SMA Pasundan 1 Cimahi - Sukmawati, Dina; Adrian; Awati Darmana, Feni (STKIP Pasundan, 2025)
This study aims to determine how the influence of political participation on novice voters ahead of the 2024 general election at Pasundan 1 Cimahi High School. The author is a quantitative researcher with a survey methodology. The instrument the author uses is a questionnaire of political participation and novice voters. The population in this study was Pasundan 1 Cimahi High School students who were 17 years old at the time of the general election, which was based on the General Election Law Chapter IV Article 198 Paragraph 1, as novice voters. The sample used amounted to 56 samples from a population of 129, with the sampling technique used being probability sampling with a simple random sampling type. Based on the results of research and discussion, it can be concluded that political participation has a significant influence on novice voters, as seen from the level of relationship between variable X, political participation, and variable Y, novice voters, which is declared